Induced ferromagnetism at BiFeO3/YBa2Cu3O7 interfaces - Wen, Xiao-Dong (2014)
Transition metal oxides (TMOs) exhibit many emergent phenomena ranging from high-temperature superconductivity and giant magnetoresistance to magnetism and ferroelectricity. In addition, when TMOs are interfaced with each other, new functionalities can arise, which are absent in individual components. Here, we report results from first-principles calculations on the magnetism at the BiFeO3/YBa2Cu3O7 interfaces. By comparing the total energy for various magnetic spin configurations inside BiFeO3, we are able to show that a metallic ferromagnetism is induced near the interface. We further develop an interface exchange-coupling model and place the extracted exchange coupling interaction strengths, from the first-principles calculations, into a resultant generic phase diagram. Our conclusion of interfacial ferromagnetism is confirmed by the presence of a hysteresis loop in field-dependent magnetization data. The emergence of interfacial ferromagnetism should have implications to electronic and transport properties.